(untitled) (Journal of Parents and Teachers, 2014)
The term "learning disabilities" is often used in the literature to refer to children with difficulties in reading, writing and maths. In this article we will take a broader perspective to outline those problems, difficulties, problems, etc. that affect school performance. The theoretical framework provided by the Theory of Multiple Intelligences is suitable for this purpose. School need to modify much of their teaching approaches. This change would benefit all students, even those who have difficulties. Educational intervention with struggling students should broaden their perspective and not focus only on e "deficit" but also on the strengths and skills.